#TITLE_ALTERNATIVE# - KURNIATI SURYAMAN (NIM : 13706048); Pembimbing : Dr. Ir. Ivindra Pane, GANISA
Corrosion of the reinforcement due to chloride penetration is one of the biggest threats to the reinforced concrete infrastructures. Structures which are exposed to chloride-rich environment are very prone to corrosion due to chloride penetration. To evaluate the chloride resistance of concrete and to predict the service life of the reinforced structures, many methods have been developed to measure the transport of chloride ions in concrete. Accelerated method is one of the methods to measure the transport of chloride ion into concrete. The purpose of this research is to know the influence of the test duration to the chloride penetration depth and chloride profile in concrete. In this research, the accelerated method for chloride penetration was used. The variations of the test duration which were used in this research are 6 hours, 12 hours and 24 hours. The value of chloride diffusion coefficient ( D ) and chloride ingress predicted time were also calculated. From the observation, it is found that the value of D from the test which was using the voltage of 60 volt, 3% NaCl solution for 24 hours is not valid. The reason for this inaccuracy is because the true chloride penetration depth could not be monitored because of the limited size of the specimen.